(untitled) (Altre Modernità, 2019)
This work aims at presenting the new educational materials proposed by Persian translators and foreigner authors such as Fénelon and Madame de Lambert whose works focused on woman’s genuine role within the Islamic community and on new cultural ideals where men should have a different attitude towards women in order to grow the new generation according to healthy and renewed principles. Through the comparative and intertextual method, this research traces the links between texts and different influences. It will be shown how Persian authors have been inspired by French writers belonging to previous literary traditions to conciliate tradition and progress.